PELICAN: A quality of life instrument for childhood asthma: Study Protocol of two Randomized Controlled Trials in Primary and Specialized Care in the Netherlands - van Bragt Stephanie; van den Bemt Lisette; Thoonen Bart; van Weel Chris; Merkus Peter; Schermer Tjard (BMC, 2012)
Abstract Background Asthma is one of the major chronic health problems in children in the Netherlands. The Pelican is a paediatric asthma-related quality of life instrument for children with asthma from 6-11 years old, which is suitable for clinical practice in primary and specialized care. Based on this instrument, we developed a self-management treatment to improve asthma-related quality of life. The Pelican intervention will be investigated in different health care settings. Results of intervention studies are often extrapolated to other health care settings than originally investigated. Because of differences in organization, disease severity, patient characteristics and care provision between health care settings, extrapolating research results could lead to unnecessary health costs without the desired health care achievements. Therefore, interventions have to be investigated in different health care settings when possible. This study is an example of an intervention study in different health care settings. In this article, we will present the study protocol of the Pelican study in primary and specialized care. Method/design This study consists of two randomized controlled trials to assess the effectiveness of the Pelican intervention in primary and specialized care. The trial in primary care is a multilevel design with 170 children with asthma in 16 general practices. All children in one general practices are allocated to the same treatment group. The trial in specialized care is a multicentre trial with 100 children with asthma. Children in one outpatient clinic are randomly allocated to the intervention or usual care group. In both trials, children will visit the care provider four times during a follow-up of nine months. This study is registered and ethically approved. Discussion This article describes the study protocol of the Pelican study in different health care settings. If the Pelican intervention proves to be effective and efficient, implementation in primary and specialized care for paediatric asthma in the Netherlands will be recommended. Trial registration This study is registered by clinicaltrial.gov (NCT01109745)